Drawing as an efficient encoding tool in younger but not always older adults: The case of associative memory. - Ovalle-Fresa, Rebecca; Martarelli, Corinna S. (Memory & Cognition, 2025)
Episodic memory strongly declines in healthy aging, at least partly because of reduced abilities to create and remember associations (associative memory) and to use efficient memory strategies. Several studies have shown that drawing the to-be-remembered material is a reliable encoding tool to enhance memory of individual items (item memory) because it simultaneously integrates elaborative, pictorial, and motoric processes. These processes in isolation can enhance associative memory in older adults. Nevertheless, their simultaneous impact on associative memory has never been investigated in drawing as an encoding tool. We aimed to investigate whether drawing as an encoding tool not only enhances item memory, but whether its benefit extends to associative memory in younger and older adults. Therefore, we tested 101 older and 100 younger participants in two online experiments and one in-person experiment. Using a memory task for unrelated word-pairs, we compared relational drawing and repeatedly writing (non-relational) as encoding tools and assessed immediate recognition memory of items and associations. In Experiment 2, we additionally assessed recognition memory after 1 week. The findings were consistent across the three experiments: while younger participants benefited from drawing over writing in item and associative memory, older participants benefited in item but not in associative memory. The observed effects remained after 1 week. Thus, we could extend the benefit of drawing to relational drawing in associative memory in younger adults. The lack of benefit in older adults' associative memory might be explained by age-related difficulties in benefiting from memory strategies, and in creating and retrieving associations.